Math, asked by harshali22, 1 year ago

3p^2+7p+1=0 solve by comleting square method

Answers

Answered by dishagaur748
3

HEY MATE!

HERE IS YOUR ANSWER:

3p^2+7p+1=0

3p^2+7p=-1

3p^2/3+7p/3=-1/3

p^2+7p/3=-1/3

p^2+7p/3+(1/2×7/3)^2=-1/3(1/2×7/3)^2

p^2+7p/3+(7/6)^2=-1/3(7/6)^2

(p+7/6)^2=-1/3×49/36

(p+7/6)^2=-49/108

As root of negative is not possible so, the equation does not have real roots.

Hope it helped ^_^

Answered by ItźDyñamicgirł
27

Answer

3 {p}^{2}  + 4 =  - 7p

3 {p}^{2}  + 7p + 4 = 0

 {p}^{2}   \:  \: \frac{7}{3} p  \:  +  \frac{4}{3}  = 0

Dividing both by sides 3

coefficient \: of \: p \: is \:  \frac{7}{3}

now ( \: { \frac{1}{2} \times  \frac{7}{3})  }^{2}  = ( { \frac{7}{6}) }^{2}  =  \frac{49}{36}

Now adding both sides by

 \frac{49}{36}

 {p}^{2}  \frac{7}{3}p +  \frac{49}{36}   =  -  \frac{4}{3}  +  \frac{49}{36}

(p +   { \frac{7}{6}) }^{2}  =   \frac{ - 48 + 49}{36}

(p +  { \frac{7}{6}) }^{2} =  \frac{1}{36}

(p +  \frac{7}{6}) =  \frac{ + 1}{6}

p =  \frac{ + 1}{6} -  \frac{7}{6}

p =  \frac{1}{6} -  \frac{7}{6} \: or \: p =  \frac{ - 1}{6} -  \frac{7}{6}

p =  - 1 \: or \: p \:  =  \frac{ - 4}{3}

hope this will help you. ..

Similar questions